Menelisik Ketuhanan Yesus dalam Frasa “Eloi Eloi Lama Sabakthani”: Analisis Tekstual Markus 15:34 - Marianus Patora; Nunuk Rinukti; Devi Maria Bungaa (SEKOLAH TINGGI AGAMA KRISTEN TERUNA BHAKTI, 2021)
There are doubts about the divinity of Jesus from non-Christian circles and the limited understanding of lay Christians in providing an explanation of the phrase Eloi Eloi Lama Sabaktani. This research is a study of the meaning of the phrase